A proposed framework for assessing the influence of internal corporate social responsibility belief on employee intention to job continuity - Sanusi, F.A. (John Wiley and Sons Ltd, 2020)
This study develops a comprehensive conceptual framework and propositions that integrate the concept of internal corporate social responsibility (ICSR) belief with employee intention to job continuity for solving the existing problem of employee's job turnover. A careful examination of existing literature on the construct of ICSR facilitates the necessity for the development of a research framework consisting of several research propositions. An integrated conceptual framework of ICSR belief and employee intention to job continuity was constructed based on the existing conceptualization of corporate social responsibility and ICSR. In addition, this paper proposes a quantitative research method to obtain information about ICSR belief and employee intention to job continuity. Questionnaire instrument will be used to collect data from the employee. The paper also proposes partial least square structural equation modeling for the proposed study analysis. Finally, the conceptual framework provides a logical path for future studies. Theoretically, the effect of ICSR on employee's job engagement was found inconclusive and requires further academic deliberation. In this study, a total number of six propositions were developed to provide an opportunity for informed decision-making that will enhance sustainable performance. The research framework and propositions were developed to cater for the need to improve management and employee relationship in the workplace to build a positive functional work environment that promotes valuable performance. This will also insight the global sustainable initiative pertaining to human resource management. Finally, completion of this study will have implications on local as well as the international labor development. Â© 2020 ERP Environment and John Wiley & Sons Ltd